Strategies For Improving Welfare In North Sumatra: A Maqashid Syariah Approach - Mufti, Robi; Nasution, Juliana; Jannah, Nurul (UNIVERSITAS PAKUAN, 2024)
North Sumatra has demonstrated a strong commitment to efforts aimed at improving the welfare of its region. Various strategic steps have been taken to achieve that goal, including in the economic, social, and environmental fields.Global development has been referring to the goals, more popularly known as the Sustainable Development Goals (SDGs), since 2015. This research is a field study using a qualitative descriptive research method with the parameters of the maqashid syari'ah index.The application of strategies in improving welfare and sustainable development in the context of maqasid sharia requires attention to several components. The preservation of religion, the preservation of life, the preservation of intellect, the preservation of lineage, and the preservation of property are included in this list of basic needs. This is because there are still communities where the five aspects of maqashid sharia have not been fulfilled, such as the preservation of religion, life, and lineage. Therefore, the people in North Sumatra have not achieved prosperity according to maqashid sharia. Here are some examples of government programs related to maqashid sharia. like the independent mosque movement program (hifdz al-din), strives to create inclusive businesses to achieve social welfare (hifdz al-nafs), innovates the Mapro program, provides Direct Cash Assistance (BLT), basic food packages, the Family Hope Program, and health insurance (Hifdz An-Nafs), innovates to support waste processing businesses (Hifdz Al-Aql), has policies to ensure transparency in public budget management (Hifdz Al-Mal), and Family Planning (KB) programs, Sexual Education in Schools, Reproductive Health Services. (Hifdz An-Nasl). Keywords: Improvement of Welfare, Maqashid Sharia.